2007
DOI: 10.1158/1078-0432.ccr-07-0142
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin E–Associated Kinase Activity Predicts Response to Platinum-Based Chemotherapy

Abstract: Purpose: The role of cyclin E as a predictive marker of response to chemotherapy remains unknown. We have previously shown that deregulation of cyclin E in an ovarian tumor cell line model enhances cyclin E^associated kinase activity and sensitizes tumor cells to cisplatinum. We hypothesized that cyclin E deregulation would predict for responsiveness to platinum-based regimens in ovarian cancer patients. Experimental Design: Patients who met the following criteria were retrospectively identified from the insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
8
10
0
Order By: Relevance
“…These data indicated that cyclin E deregulation is an important event in ovarian tumorigenesis in vivo and are consistent with the high frequency of cyclin E overexpression reported in primary ovarian tumors (12)(13)(14)(15)(16)(17)(18)(19). Notably, whenever Western blot analysis has been used to assess cyclin E protein expression, a clear correlation has been found between the overexpression of cyclin EL1 and its LMW isoforms (15,16,18). To our knowledge, only three published studies in addition to our own have assessed cyclin E expression in ovarian tumors by Western blotting, which has the advantage over the more commonly used immunohistochemical approach in that it is able to distinguish the various isoforms of cyclin E. Thus, it is possible that the contribution of LMW isoform expression to ovarian cancer development (and potentially the development of other types of cancer) has, to-date, been underestimated.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…These data indicated that cyclin E deregulation is an important event in ovarian tumorigenesis in vivo and are consistent with the high frequency of cyclin E overexpression reported in primary ovarian tumors (12)(13)(14)(15)(16)(17)(18)(19). Notably, whenever Western blot analysis has been used to assess cyclin E protein expression, a clear correlation has been found between the overexpression of cyclin EL1 and its LMW isoforms (15,16,18). To our knowledge, only three published studies in addition to our own have assessed cyclin E expression in ovarian tumors by Western blotting, which has the advantage over the more commonly used immunohistochemical approach in that it is able to distinguish the various isoforms of cyclin E. Thus, it is possible that the contribution of LMW isoform expression to ovarian cancer development (and potentially the development of other types of cancer) has, to-date, been underestimated.…”
Section: Discussionsupporting
confidence: 88%
“…These data indicated that cyclin E deregulation is an important event in ovarian tumorigenesis in vivo and are consistent with the high frequency of cyclin E overexpression reported in primary ovarian tumors (12)(13)(14)(15)(16)(17)(18)(19). Notably, whenever Western blot analysis has been used to assess cyclin E protein expression, a clear correlation has been found between the overexpression of cyclin EL1 and its LMW isoforms (15,16,18).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations